Notas sobre la ecología trófica de una población de Proctoporus chasqui (Squamata;Gymnophthalmidae) en bosques montanos del sur del Perú - Diaz Vargas, Vladimir (2025)
This study analyzes the diet composition and seasonal variation of Proctoporus chasqui in a population of Chiquintirca, Ayacucho, Peru. The fieldwork was carried out during the wet (October 2018) and dry (June 2019) seasons. Analysis of the stomach contents of 18 individuals revealed 105 preys grouped into 11 dietary categories. Coleoptera (19.05%) was the most abundant type of prey, followed by Hemiptera (16.19%) and Araneae (16.19%). In terms of volume, Araneae (28.66%) dominated, followed by Coleoptera (12.92%) and Hemiptera (8.29%). The most frequent prey was Coleoptera (61.11%), while plant material was present in 50% of the individuals, but only contributed 8.57% in number and 4.27% in volume. Species exhibited seasonal changes in diet: during the wet season, beetles (39.96%) and winged hymenoptera (21.02%) were dominant prey, while in the dry season, hemiptera (33.82%) and plant material (32.30%) increased in proportion. The amplitude of the trophic niche (Bij) was 7.37, varying from 5.15 in the wet season to 5.29 in the dry season. These results classify P. chasqui as an insectivorous generalist with seasonal omnivorous tendencies and would have a "sit and wait" feeding strategy. This study provides the first documented evidence of plant consumption in Proctoporus, suggesting that dietary flexibility may be an adaptive response to fluctuating food availability in mountainous environments. Understanding such trophic adaptations is crucial to assessing the ecological dynamics of high-altitude reptile communities in the tropical Andes.